FEUDALISM IN THE ABUSE OF POWER IN URSULA K. LE GUIN’S SEMLEY’S NECKLACE - Amalia Farhati; Hadiyanto Hadiyanto (Department of Linguistics, Faculty of Humanities, Diponegoro University, 2021)
Abstract This research paper discusses feudalism in the short story written by Ursula K. Le Guin, entitled Semley’s Necklace. The writers use sociological approach to analyze the textual and contextual elements in the story. The writers apply library research method in compiling data and information needed related to the research. In analyzing the phenomena in Ursula K. Le Guin’s Semley’s Necklace, the writers use the theory of Feudalism of François-Louis Ganshof and Marc Bloch. The result of the research indicates that there is a partnership inequality between the Lord-Vassal feudal system and the abuses of power committed by the Starlords as the ruling party that fails to prosper the inhabitants of Western Lands and exploits their property. The exploitation causes a rampant growth of poverty in Western Lands. The poverty causes discontent and jealousy on Semley as the protagonist in the story. The poverty, discontent, and jealousy bring Semley influence to decide to leave the manor to search for her lost dowry called “The Eye of the Sea”. As a result, Semley loses her beloved husband, the only reason she goes away to bring back her sapphire-stoned necklace in a “one-night long” journey. Keywords: feudalism, abuse of power, lord, vassal